A Mixed-Methods Study on Student Transferring from Public to Private in Santa Rosa City - Babiano, Emilia H.; Montillano, Allen Cris (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This case study investigates the experiences of public-school pupils transferring to private schools, focusing on the complexities and outcomes of such transitions. The research identifies seven key themes: the role of students in educational decision-making, school choice and educational quality, parental expectations of school leadership and management, the academic impact of school transfers on students, transitional challenges to new schools, holistic academic growth and personal development, and parental support for transferred students facing challenges. The participants of the study were 30 pupils who are transferees from public school for the current school year and 10 parents of this pupils for a total of 40 participants. Through qualitative and quantitative data analysis, the study highlights the importance of supportive and well-managed transitions to ensure students' academic success and personal development. Recommendations include enhancing communication channels, providing school choice guidance, implementing targeted academic support programs, and fostering holistic development through extracurricular activities and personal growth workshops. The findings underscore the need for comprehensive transition programs and continuous feedback mechanisms to address the multifaceted challenges faced by transferring students. Ultimately, understanding the motivations behind these transfers, the challenges students face, and the importance of support systems is crucial for educators and policymakers in both public and private sectors. By addressing the needs of transferring students and fostering a smooth integration into their new educational environments, we can contribute to positive student outcomes and a deeper understanding of the dynamics of school choice.